2003
DOI: 10.1002/bsl.542
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a mental health treatment court with assertive community treatment

Abstract: Without active engagement, many adults with serious mental illnesses remain untreated in the community and commit criminal offenses, resulting in their placement in the jails rather than mental health facilities. A mental health treatment court (MHTC) with an assertive community treatment (ACT) model of case management was developed through the cooperative efforts of the criminal justice and mental health systems. Participants were 235 adults with a serious mental illness who were booked into the county jail, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
119
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(124 citation statements)
references
References 26 publications
4
119
0
Order By: Relevance
“…The increase in life satisfaction during the follow-up period in both groups was subtle even though previous studies demonstrated an increase in life satisfaction following the ACT program [26,27]. Our result is consistent with a Japanese study reporting that the ACT program had no significant relationship with life satisfaction [28].…”
Section: Discussionsupporting
confidence: 87%
“…The increase in life satisfaction during the follow-up period in both groups was subtle even though previous studies demonstrated an increase in life satisfaction following the ACT program [26,27]. Our result is consistent with a Japanese study reporting that the ACT program had no significant relationship with life satisfaction [28].…”
Section: Discussionsupporting
confidence: 87%
“…The Broward study has produced a series of papers on the operation of the court (Petrila, Poythress, McGaha, & Boothroyd, 2001;Poythress, Petrila, McGaha, & Boothroyd, 2002), and the characteristics and service use of the participants (Boothroyd et al, 2003), with analyses on participant outcomes now being conducted. The Santa Barbara study was a randomized control trial comparing a MHC participant sample and a treatment-as-usual (control) sample (Cosden, Ellens, Schnell, Yasmeen, & Wolfe, 2003). Both samples had been referred and found eligible for the MHC, but were randomly assigned into their respective groupings.…”
Section: Gaps In the Knowledge Base Of Mental Health Courtsmentioning
confidence: 99%
“…38,39 Persons with a serious and pervasive mental illness who were randomized to a mental health treatment court with an assertive community treatment model of case management experienced greater improvements in mental health status, functioning, and drug use, but not quality of life or alcohol use, compared with treatment as usual. 77 In persons who were seriously mentally ill and homeless, there was no difference in mental health, alcohol and drug use, or quality of life at 1 year after release among those randomized to an assertive community treatment team, forensic specialist case managers based in community mental health agencies, or referral to a community mental health center. 124,125 …”
Section: Mental Health Interventionsmentioning
confidence: 98%
“…Services after release-Three interventions were implemented in the community after release, 38,39,77,124,125 and 2 of these positively affected substance abuse outcomes. 38,39,77 In adults on parole who received daily, automated phone assessment in the month after release, the addition of feedback and a recommendation led to greater improvements in mental health and drug and alcohol use.…”
Section: Mental Health Interventionsmentioning
confidence: 99%
See 1 more Smart Citation